2017
DOI: 10.1007/s12192-017-0801-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of myocardial heat shock proteins in rats acutely exposed to fluoride

Abstract: Acute fluoride (F − ) toxicity is known to cause severe cardiac complications and leads to sudden heart failure. Previously, we reported that increased myocardial oxidative damage, apoptosis, altered cytoskeleton and AMPK signaling proteins associated with energy deprivation in acute F − induced cardiac dysfunction. The present study was aimed to decipher the status of myocardial heat shock proteins (HspsHsp27, Hsp32, Hsp40, Hsp60, Hsp70, Hsp90) and heat shock transcription factor 1 (Hsf1) in acute F − -intoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
(45 reference statements)
0
8
0
2
Order By: Relevance
“…145 In this model, HSP60 overexpression is suggested to result from increased apoptotic and oxidative events induced by acute Fl − toxicity. 145 Chronic hypersympathetic activity is a frequent finding in HF as indicated by high resting heart rate (HR). In an organ with an already compromised contractility, persistent stimulation by the sympathetic nervous system (SNS) implies increasing the workload the heart is subjected to, and the resulting stress this system is endowed with activates endogenous defense mechanisms, including the HSPs response.…”
Section: Heart Failurementioning
confidence: 95%
See 3 more Smart Citations
“…145 In this model, HSP60 overexpression is suggested to result from increased apoptotic and oxidative events induced by acute Fl − toxicity. 145 Chronic hypersympathetic activity is a frequent finding in HF as indicated by high resting heart rate (HR). In an organ with an already compromised contractility, persistent stimulation by the sympathetic nervous system (SNS) implies increasing the workload the heart is subjected to, and the resulting stress this system is endowed with activates endogenous defense mechanisms, including the HSPs response.…”
Section: Heart Failurementioning
confidence: 95%
“…A dose-dependent increase in both myocardial transcript and protein levels for HSPs and HSF-1 including HSP70, HSP60, HSP32, and HSP27 was reported, while an inverse pattern was observed for HSP40 and HSP90. 145 In this model, HSP60 overexpression is suggested to result from increased apoptotic and oxidative events induced by acute Fl − toxicity. 145 Chronic hypersympathetic activity is a frequent finding in HF as indicated by high resting heart rate (HR).…”
Section: Heart Failurementioning
confidence: 95%
See 2 more Smart Citations
“…In vivo studies using animal models have found that chronic F exposure can modulate the expression of heat shock proteins in cardiac tissue, liver, kidney and testes [ 204 , 205 , 206 ]. Recently, Panneerselvam et al demonstrated that F significantly downregulated the expression of heat shock protein 40 (Hsp40) within living mammalian cells in vivo and upregulated HsP27 and Hsp70 [ 204 ]. Consistent with this, Zhao et al also found that F upregulated mRNA and proteins levels of Hsf27 [ 205 ].…”
Section: Molecular Mechanisms Underlying Fluoride Contribution To mentioning
confidence: 99%